1995
DOI: 10.22358/jafs/69783/1995
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of energy and protein utilization by growing pigs fed diets containing both full-fat rape seeds and rapeseed meal

Abstract: Twenty-four Polish Landrace pigs (12 gilts and 12 barrows) fattened from 30 to 95 kg body weight were fed diets containing 18% rapeseed meal (RSM) and full-fat rape seeds (RS) in the following amounts: 0 (group RS-0), 10 (group RS-10) or 20% (group RS-20). The pigs were fed on an individual basis with rations having equal energy, protein and lysine contents. Nitrogen balance was determined at 40, 60 and 80 kg liveweight. Metabolizable energy and protein utilization were determined by the slaughter technique. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Raj et al (22) recently reported that, as the proportion of rapeseed substituting for barley in pig diets increased, average daily gain decreased. However, in the present study, there was no evidence of any effect of whole rapeseed on daily gain, although values for pigs fed diet CD200 were noticeably, but not significantly, higher than the other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Raj et al (22) recently reported that, as the proportion of rapeseed substituting for barley in pig diets increased, average daily gain decreased. However, in the present study, there was no evidence of any effect of whole rapeseed on daily gain, although values for pigs fed diet CD200 were noticeably, but not significantly, higher than the other treatments.…”
Section: Discussionmentioning
confidence: 99%